Bimbingan Agama Melalui Ta’limah dalam Membentuk Kepercayaan Diri Tunanetra - Madaniyah, Nurul Fajri Fitri; Karim, Abdul; Hidayanti, Ema; Nihayah, Ulin (Institut Agama Islam Negeri Kerinci, 2023)
Disabilities have various psychological problems, one of the important psychological problems is self-confidence. Disabilities generally experience problems of self-confidence due to negative stigma from other people and feel inferior due to deficiencies that exist in themselves. Forming self-confidence in distractions is important for distractions, one of which is with religious assistance through ta'limah. This qualitative research aims to describe religious guidance through ta'limah in shaping the self-confidence of persons with visual disabilities. This type of research uses case studies at the “Majelis Pengajian Difabel” Semarang City. This study involved four main informants. As for this research, the techniques used are observation techniques, interviews and documentation techniques. The data analysis technique in this study was the analysis from Milles and Huberman, with the stages of data reduction, data presentation, and conclusions. The results of the research obtained from religious guidance through ta'limah in forming self-confidence in blind disorders, namely religious guidance through ta'limah at the Disability Study Assembly can form self-confidence by providing religious studies and sharing among disabled people through lecture and discussion methods. From various aspects of self-confidence, it is shown in the aspects of self-confidence, optimism, and responsibility that emerged after the blind disorder participated in the study of the “Majelis Pengajian Difabel” Semarang City